Pengaruh Aktivitas Live Streaming dan Ulasan Cutomer Terhadap Keputusan Pembelian dengan Variabel Moderasi Minat Beli pada E-Marketplace Shopee (Studi pada UMKM Nusantara Jaya Fashion) - Mordek Hay Manurung; Alexander Mario Retto Djong; Truli Nugroho; Kristian Faskahariyanto (STIE AUB Surakarta, 2025)
This research aims to analyze the influence of live streaming and customer reviews on purchasing decisions with purchase interest as a moderating variable. The population in this study is Nusantara Jaya Fashion UMKM consumers during January 2025 until March 2025 totaling 12,362 consumers. This research uses an associative quantitative with primary data as a data source. The sampling technique used is probability sampling method with a random sampling approach, by calculating slovin, so the sample 99 samples were obtained. The data analysis methods in this research are, data quality test, Classical Assumption Test, Moderated Regression Analysis (MRA). The research results show that live streaming and customer reviews have a significant influence on purchasing decisions. However, buying interest did not show any significant impact on purchasing decisions. Meanwhile, buying interest as a moderation variable, unable to moderate live streaming and customer reviews on purchasing decisions.